PERSPEKTIF POSITIF PRAKTIK MANAJEMEN LABA: KAJIAN EMPIRIS PADA PERUSAHAAN MANUFAKTUR GO PUBLIK DI BURSA EFEK INDONESIA - Wiyadi Wiyadi; Nur Amalina; Rina Trisnawati; Noer Sasongko (Riset Akuntansi dan Keuangan Indonesia, 2017)
The earnings management practice has a positive and negative perspectives. This study aimed to analyze the effect of earnings management, corporate performance, quality audits, and Investment opportunity set to cost of equity companies are included in the Islamic index (JII) and conventional index (LQ-45). Measuring the earnings management used a short-term discretionary accruals (STDA) model. There were 461 companies (257 companies LQ-45 and 204 companies JII) taken by purposive sampling. Data was analyzed using multiple linear regression. Result of the data analysis showed that earnings management and company performance has no significantly effect on the cost of equity in both companies as well as JII and LQ-45. The quality of audit has significantly effect on the cost of equity in the JII companies, but had not significantly effect on the LQ-45 companies. And the investment opportunity set significantly effect on the cost of equity as well as in both of JII and LQ-45 companies. This indicates the earnings management in Indonesia tend to use a negative or opportunistic perspectives. Keywords: earnings management, corporate performance, quality audits, investment opportunity set, cost of equity capital.